Pembentukan Karakter Anak Usia Dini: Keluarga, Sekolah, Dan Komunitas? (Studi Kualitatif tentang Pembentukan Karakter Anak Usia Dini Melalui Keluarga, Sekolah, dan Komunitas) - Ditha Prasanti; Dinda Rakhma Fitriani (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
Without realizing it, the development of the child's character does not appear spontaneously. There is a process that is experienced and passed, one of which is the development phase. The earliest character development period is for early childhood. How important are parents to notice the formation of the character of the early childhood they have. When talking about the formation of early childhood characters, we become reminded of the environmental and family factors that are close to the child. In this article, the author wants to discuss about the process of character building early childhood in three elements; family, school, and community. Based on the results of the study conducted, the authors found that the process of forming the character of early childhood, beginning from the family, then followed by the school, and the community followed by these early childhood. This community includes the play community, the tutoring community or the talent development course institution that the early childhood participates in. But, the main determining factor is the family as the smallest and first community for the children.